International legal responsibility of states for the pollution of the oceans - B. Valiullina, Ksenia (2018)
The entry of the world community into the 21st century was characterized by the recognition of the exceptional importance and necessity of stabilizing international relations in all important areas. The pristine beauty of our fragile world can only be preserved if the global, regional, economic, environmental and social issues would be resolved in a reasonable and timely manner, and the proper order in the world to be established. In this regard, the cooperation of states has become not only an obligatory principle of international law, but also an indispensable condition for global development. So, back in 1997 the UN General Assembly called on all states to carry out their activities in accordance with the norms of international law, and above all in accordance with the UN Charter, to promote respect for and implementation of international legal principles, to join multilateral agreements in order to promote the development of international law in general and all its branches. The most important principle of international law is the principle of conscientious fulfillment by states of their international obligations. States parties to international conventions undertake to fulfill their obligations in good faith arising from generally recognized principles and norms of international law, as well as obligations resulting from other international treaties and agreements to which they are parties. In the exercise of their sovereign rights, including the right to establish their laws and administrative rules, they will align them with their legal obligations under international law. Thus, an essential sign of the principle pacta sunt servanda (from Latin "treaties must be respected") is the implementation on a voluntary basis by all participants of international legal relations of all undertaken obligations and the non-admission of rejection of them unilaterally. The protection of the World Ocean is connected with the adoption of a number of preventive measures, the monitoring of compliance with which is entrusted to international bodies specified in international agreements. In the case, when there is a fact of pollution, or their violation, the process of adopting a number of measures aimed at combating the consequences, namely, the protection of the World Ocean from pollution, which, in some cases, involves bringing to international responsibility, begins. In the international legal doctrine, the problem of the international responsibility of states is one of the most controversial. There are different definitions of the responsibility of states, but all without exception recognize the fact that it plays a crucial role in maintaining law.